Pengaruh Lingkungan Belajar Dan Konsep Diri Terhadap Hasil Belajar Biologi Siswa SMP Negeri I Maluku Tengah - Pebrywati Watimury; Farida Bahalwan (BIOSEL (Biology Science and Education): Jurnal Penelitian Science dan Pendidikan, 2019)
The purpose of this study was to determine the effect of the learning environment on the learning outcomes of Central Moluccas I Middle School student biologists. Knowing the effect of self-concept on the biology learning outcomes of students of Central Maluku Middle School I and find out the effect of the learning environment and self-concept together on the biology learning outcomes of Central Maluku Middle School I students. This type of research is ex-postfacto research with data collection techniques through questionnaires and student test scores of descriptive and inferential data analysis techniques (multiple regression). The results show that. (1) there is a significant influence between the learning environment on the biology learning outcomes of Central Maluku Middle School I students, (2) there is a significant influence between self-concept towards student biology learning outcomes, and (3) there is a significant influence between the learning environment and simultaneously on the achievement of biology learning. Key Words: Learning Environment, Self Concept, Learning Outcomes